The Structural Dilemma of Citizen Participation: The Interactive Influence of Social Status and Subjective Social Mobility. (April 2021) - Tan, Xuyun; Dou, Xuejiao; Zhang, Yue; Xing, Cai; Bai, Baoyu; Miao, Ruikai
In the context of rapid social change, the perception of social stratification has far-reaching and complex influences on human psychology and behavior, including citizen participation. The current research explored the interactive influence of social status and subjective social mobility on citizen participation. Two studies used experimental methods to manipulate subjective social mobility and social status, respectively, to examine the interactive effect. Taken together, the results of both studies revealed that the interaction between social status and subjective social mobility had a significant influence on citizen participation: whereas citizen participation with high social status was not affected by subjective social mobility, citizen participation with low social status decreased with increases in subjective social mobility. This research established a combined dynamic and static analysis framework of social stratification structure, elucidating the current status of citizen participation under the influence of the interaction between social status and subjective social mobility, and providing a countermeasure reference for effectively promoting citizen participation.